2016
DOI: 10.1177/0266666915597546
|View full text |Cite
|
Sign up to set email alerts
|

The influence of learning value on learning management system use

Abstract: In this study the perceived value construct of the Unified Theory of Acceptance and Use of Technology (UTAUT2) is investigated in the context of a learning management system (LMS), in which the construct is redefined from its original price value conceptualization. It was found that many researchers simply ignore the price value construct when applying the UTAUT2 model in technology use studies in the educational context. This study extends the UTAUT2 framework by integrating the learning value construct and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
264
11
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(316 citation statements)
references
References 48 publications
31
264
11
10
Order By: Relevance
“…It is however important to add that PE was only significant at an error of 10% but insignificant to BI at p<0.05, which is consistent with results by Jairak et al, (2009), while the effect of Social influence being insignificant to BI, confirmed the findings of Nassuora (2012). These results disagree with that of Venkatesh et al, (2003), Khechine et al, (2014) and Ain et al, (2015). …”
Section: Summary Of Findingssupporting
confidence: 87%
“…It is however important to add that PE was only significant at an error of 10% but insignificant to BI at p<0.05, which is consistent with results by Jairak et al, (2009), while the effect of Social influence being insignificant to BI, confirmed the findings of Nassuora (2012). These results disagree with that of Venkatesh et al, (2003), Khechine et al, (2014) and Ain et al, (2015). …”
Section: Summary Of Findingssupporting
confidence: 87%
“…The reliability and consistency of the UTAUT model is found to be applicable, reliable, accurate and in uniformity with the original UTAUT (Venkatesh et. al 2013), and other studies on general acceptance and usage of technology (Anderson and Schwager 2004;Louho, Kallioja and Oittinen 2006;Kripanont 2007;Schaper and Pervan 2007;Ain, Kaur and Waheed 2015). These results have an important implication on the theoretical foundation of the unified theory and strongly supports the conjecture of a unified view of technology acceptance.…”
Section: Performance Of the Validated Adapted Modelsupporting
confidence: 63%
“…Waheed et al (2015) and Ain et al (2015) reported a significant direct effect of PE on behavioural intention to use a technology. It is assumed that librarian belief that RFID-LMS will be useful in their tasks leads to the justification of examining PE as a determinant in this study.…”
Section: Performance Expectancy (Pe)mentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have also confirmed the influence of behavioral intention on usage behavior; Ain et al [40], Dečman [21], Chiu & Wang [41], Pynoo et al [23], and Wang et al [23],…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 85%